Débattre ou apprendre : faut-il choisir ? - Patrice Raynaud Serra
In between the consumption of culture, Humanitas, and the ideology where man is given once for all by the Humanists, this article attempts to find a median way where learn looks like debate and so escapes from all control provided by the knowing for the power. From the Platoon's dialectical way that we found by a lecture of Hannah Arendt's and Peter Sloterdijk's writings, we search how to go back down into the cavern with an invisible term which opens debate.